2018 IEEE 29th Annual International Symposium on Personal, Indoor and Mobile Radio Communications (PIMRC) 2018
DOI: 10.1109/pimrc.2018.8580991
|View full text |Cite
|
Sign up to set email alerts
|

ToA-based Iterative Localization in Rich Multipath Channels

Abstract: Iterative localization is arising as a promising solution to determine the position of a mobile station in a cellular network. We recently showed that in a perfect lineof-sight environment, iterating between the conventional delay estimation and multi-lateration steps allows to approach the performance of the direct localization based on the observation of the received signals. In this paper we extend our iterative localization method to operate in rich multipath environments. Simulation results prove that giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In addition, we can define the likelihood of the received signal at BS-i based on (8). More precisely, such likelihood can be modeled as a Gaussian distribution as…”
Section: A Centralized Direct Position Estimationmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, we can define the likelihood of the received signal at BS-i based on (8). More precisely, such likelihood can be modeled as a Gaussian distribution as…”
Section: A Centralized Direct Position Estimationmentioning
confidence: 99%
“…For instance IPE was extended in [7] to consider a time offset between transmitter and BSs, which can be directly related to this paper. In [8], IPE was extended for rich multipath scenarios which can be addressed in the SSPE framework by modifying the likelihood of the received signal.…”
Section: Sspe and Ipe Algorithm Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…Such range prior is then fed back to the BS to refine the range estimation in the first step. Moreover, the IPE algorithm introduces an iterative framework that has been extended and studied more in depth in [7] and [8] where the effect of multipath channels and time-misalignment between transmitter and receiver was studied over the algorithm. Finally, it has been also shown that the iterative framework proposed by the IPE algorithm could be used in different applications and scenarios such as angle of arrival (AOA)-based iterative localization [9] and localization on WLAN-like systems [10].…”
Section: Introductionmentioning
confidence: 99%